(untitled) (Research, Society and Development, 2025)
Among the various materials used in the composition of biomedical implants, titanium alloys (Ti) stand out, mainly the β-phase ternary alloys. The Ti10Mo8Nb alloy developed in an electric arc furnace and rotary forging was analyzed and showed adequate mechanical properties. However, its corrosion resistance has not been deeply investigated in the literature. This research aims to investigate the corrosion resistance and bacterial proliferation of β-phase alloys composed of titanium, molybdenum and niobium (Ti10Mo8Nb).For corrosion analysis, a passive current density of 4.2∙10-5 A/cm² and a dissolution potential of 1.5 V were obtained. Its biocompatibility tests, based on bacterial proliferation was 12.3% lower than that of commercially pure Ti. Combined with the mechanical characteristics of Ti10Mo8Nb, the alloy presented potential and advantageous properties to make it applicable in the field of biomedical application.